100 Years Since the Birth of prof. Kosta Pergelov - Stoyanov, Stoyan; Feschiyan, Daniela; Savova, Kameliya (Research Papers, 2023)
The paper presents brief biographical data about Prof. Kosta Pergelov. His conviction for learning as a way of deep perception of knowledge and their creative assimilation, for thinking as a supreme manifestation of human existence is revealed. Prof. Kosta Pergelov’s long and inspiring teaching activity at UNWE is interpreted through the disciplines developed and taught by him, his research publications in the field of theory and applied manifestation of accounting, his active participation in the academic and social life of Bulgaria. The plenary report focuses on the contributions of Prof. Pergelov on the nature and importance of theoretical accounting knowledge. He substantiates it through the objective laws of knowledge and develops the value theory in accounting. The duality and equivalence of economic operations are bound by the Law of Eternal Movement and Preservation of Matter. Prof. Pergelov’s rich work contributes to and affirms the indisputable scientific, historical durability and permanence of accounting knowledge.